Effect of On-demand Inhalation of Dry Oxygen on Nasal Mucociliary Clearance - Kawakami, Masahiko; Takizawa, Jun; Nakamura, Seeichi; Mori, Yutaka (Nihon Kyōbu Shikkan Gakkai zasshi, 1996)
Aim: To determine whether nasal mucociliary clearance is affected by dry oxygen delivered on demand. Methods: Saccharin nasal transit time was measured as an index of nasal mucociliary clearance. One group of patients was given dry oxygen via a nasal cannula and a demand delivery system, and another group was given dry oxygen by continuous inhalation. In each group, continuous inhalation of humidified oxygen seved as the control. Saccharin transit time was measured before and after 8 hours of oxygen inhalation. Subjects: The subjects were 25 patients with chronic respiratory failure who were receiving home oxygen therapy via nasal cannula. All the subjects were clinically stable (age 72±1, mean±SE), %VC 46.6±3.0, FEV1/FVC% 9.0±4.5, PaO2 55.7±2.0Torr, PaCO2 53.9±1.9Torr). Results: Saccharin transit time after inhalation of dry oxygen on demand did not differ from that after continuous inhalation of humidified oxygen (15.6±1.5 vs 14.9±1.4min). Saccharin transit time after continuous inhalation of dry oxygen was significantly lower than that after continuous inhalation of humidified oxygen (26.6±5.4 vs 16.7±2.6min, p<0.05). Conclusion: We conclude that using the demand oxygen delivery system with a nasal cannula for 8 hours had no adverse effects on nasal mucociliary clearance.